A INVISIBILIDADE DA MULHER NEGRA MARANHENSE NO ESTUDO SOBRE A FORMAÇÃO DA PROFESSORA NA ESCOLA NORMAL PÚBLICA EM SÃO LUÍS (1930-1945) - Rodrigues, Fernanda Lopes (2011)
This text examines discourses about the presence of black women, as a student of the training course for the public teaching of the Normal School, from 1930 to 1945, in São Luís - MA. Aims to present the results of historical research on the conditions of its formation, as well as the requirements that they were placed. The documentary sources were: the processes of public education, reports the intervening federal and directors of public instruction, editions of the Diário Oficial da União and the newspapers "O Imparcial" and "A Voz do Norte" as well as texts of legislation and educational works pedagogical published by intellectuals at the time. This analysis intended to answer the following questions: What were the demands of the black woman teacher in the education of Maranhão? What are the conditions for training in teaching? How eugenics discourse was socialized in this course? What are the meanings of black women's access to the Normal Course and her acting in teaching? It would be a strategy of whitening black students? To answer these questions were elected as analytical categories gender and race / ethnicity, learning to their connections and implications for research subjects. In this sense, were fundamental studies of Guimarães (2003, 2008), Hahner (2003), Hofbauer (2006), Louro (2010), Meyer (2003), Santos (2005) and Scott (1990), among others. Was taken as a common thread of analysis the eugenics movement in the Brazilian scenario and discusses its consequences in defining the role of the school and the social function of teachers, especially those responsible for primary education. Option that has been sustained in the work of Davila (2006), Diwan (2007) and Viviani (2007). The collected material was developed to study the offer and the operating conditions of primary school in São Luís, the principal place of operation, as well as training of future students of the Normal School. We analyzed also the conceptions about teaching, how to enter, structure and functioning of the Normal Public School in São Luís. Therefore, studies were indispensable history of education such as Robinson (1993), Sousa (2008), Veiga (2007), Vianna (2002), Vicentini & Lugli (2002). Were discussed also the causes of silencing on the ethnic-racial black students of the Normal School, highlighting the conclusion that the normal work as a means of laundering of black students. To do this, have become as essential studies Munanga (1999), Schumaher & Brazil (2007) and Skidmore (1976), among others. Based on Foucault's notion that the diffuse power in the social context is not under the control of anyone, we sought to understand the strategies of resistance to the discourses that defined places and postures to the woman teacher from a misogynist and racist vision.